Analysis of Maternal Mortality with Time; a Case Study of the Okomfo Anokye Teaching Hospital – Kumasi (2000-2010) - Asomaning, Sarpong Smart (2012)
A Thesis submitted to the Department of Mathematics, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of MASTER OF PHILOSOPHY